Pemberian Edukasi Berbasis Multimedia terhadap Kemampuan Perawatan Diri Pasien Kanker Kolorectal dengan Stoma - Retnoningrum, Dwi; Dahlia, Debie (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effectiveness of providing multimedia-based education on self-care of colorectal cancer patients with stomas. The research method used was a systematic review on four databases, namely Pubmed, Science Direct, ProQuest and Scopus with the keywords "colorectal cancer" OR "patient with stoma", AND "stoma education" OR "stoma management education", AND "self care", OR "self management" with the inclusion criteria of colorectal cancer patients, age> 18 years, from 2013 to 2023. The number of initial search articles was 4377 articles with 8 articles used. The results of the study obtained 8 articles which were then analyzed. In conclusion, the use of multimedia with OMRE, MELP, video (DVD), audiovisual, telehealth and mobile health applications to provide stoma care education can have an effective effect in increasing knowledge and self-care. In addition, it also has an effect on improving psychosocial adaptation and quality of life in colorectal cancer patients with stomas. Keywords: Education, Stoma Care, Multimedia, Self Care